RF TRANSMITTING POWER DETECTION USING RF POWER DETECTOR - Jagdev Singh, Balvinder Singh (IRC, 2019)
Radio Frequency power detection are at the frontier of its development in the engineering field. Almost every electronic device communicates through the usage of radio frequencies or RF. An RF detector monitors or samples the output of an RF circuit and develops a dc output voltage proportional to the power at that point. RF power are measured in terms of their transmitting power in decibels or dB. However, the main challenges when it comes to designing a RF power detector are the type of RF power detector, its input frequency range, input power range, and the cost to manufacture or fabricate a RF power detector. It also important to be able to accurately detect the incoming RF power to measure and control the transmitting power. There are three commonly known types of RF power detectors which are the Root Mean Square (RMS), Logarithmic power detector and Peak Detection using Schottky Diode. Each of these three has its advantages and disadvantages. The methodologies used for this project involves conducting substantial research in determining the suitable type of RF power detector, identifying the type of RF input signal and circuit modelling and simulation in order to achieve the desirable output voltage based on input signal using the KeySight Advanced Design System (ADS) circuit simulation software.